The Perpetual Patriarchy And How Dangdut Music Deals With It In A Study Of Semiotic Analysis - Meifilina, Andiwi; Saputra, Jumadil (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2024)
Dangdut music is now synonymous with the expression of sexuality. The dangdut phenomenon is actually a national phenomenon, with the concept of selling sexuality becoming a trading strategy by carrying out stage tricks that approach cultural hyperreality that also perpetuate patriarchal culture for dangdut songs dominated by sexuality. This is in contrast to dangdut songs with a religious genre that have a mission of resistance and victory over the patriarchal system. The purpose of this study is to analyze and compare the semiotics of the representation of power over sexuality in the dangdut song “Duo Semangka” and the religious genre dangdut song “Nasida Ria”. This study is different from previous studies because previous studies have revealed more erotic dancing while this study reveals video clips that are used as points of sensuality along with song lyrics that contain erotic elements and a comparison of religious song lyrics. This qualitative research uses Roland Barthes› semiotic method for the investigation of symbols, forming an important tradition of thought in communication theories. Roland Barthes sees deeper meanings at a more conventional level, namely denotative, connotative and mythical meanings. This study categorizes the patriarchal power found in Duo Semangka dangdut music into five parts, namely the female body, women as seducers of men, relations between men and women and women as objects of men›s gaze and the hyperreality of stage tricks that perpetuate patriarchy. The existence of cultural deviations in patriarchy means that there must be special efforts in implementing the propriety of art and culture. The occurrence of a cultural crisis must be returned to the musical order that is in accordance with the nation›s culture. It is necessary to continue to support dangdut artists to create works with religious themes and pride in the nation›s culture. Steps to balance patriarchal culture in dangdut song lyrics and video clips can be done by raising awareness of patriarchal culture. Furthermore, supporting social change and policies in gender equality in dangdut entertainment songs and video clips. Prioritizing male awareness of social change and becoming agents of change in changing this social norm. There needs to be a dangdut singer who has a mission to fight to cut down on patriarchal culture and show a voice of resistance against social construction that is very gender biased.